Field notes contributed by Lee A. Schoenewe, summer 2001 - Schoenewe, Lee A.et al (2001)
List of birds and locations contributed by Lee Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2001. Epson - sheet feed